Journeys with a mission: Travel journals of The Right Revd George Smith (1815-1871), first bishop of Victoria (Hong Kong) (1849-1865). Edited by Gillian Bickley. Pp. VII + 403 incl. 8 ill., Hong Kong, Proverse Hong Kong, 2018. £30 (paper). 978 988 8491 51 3 - Morrison, Hugh (The journal of ecclesiastical history, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0022046920000822/resource/name/firstPage-S0022046920000822a.jpg